Gene therapy advancements for the treatment of acquired and hereditary hearing loss - Duhon, Bailey H.; Bielefeld, Eric C.; Ren, Yin; Naidoo, Jerusha (Frontiers in Audiology and Otology, 2024)
Greater understanding of the molecular intricacies of acquired and hereditary hearing loss has spurred considerable advances in inner ear gene therapy. While approaches like cochlear amplification and cochlear implantation offer varying degrees of efficacy in restoring hearing function, there is an absence of FDA-approved pharmacotherapies targeting the underlying causes of hearing loss. Recent preclinical investigations have demonstrated promising outcomes in murine and non-human primate models, demonstrating efficient transduction and hearing recovery for both acquired and hereditary forms of hearing loss. This review provides a comprehensive analysis of the latest developments in gene therapy for hearing loss. Specifically, we focus on conditions characterized by sensory epithelium and spiral ganglion neuron dysfunction, encompassing both hereditary and acquired etiologies. We discuss recent preclinical advancements in cell-type-specific transduction strategies and highlight key findings from clinical trials exploring gene therapy interventions for hearing loss. Additionally, we address current limitations and offer insights into future directions for advancing gene therapy as a viable treatment option for individuals with hearing loss.